HOPKIN CRITERIA IN BOOK ENTITLED “BUSINESS BASIC I” USED FOR STUDENT AT UNIVERSITY - Piping Rahadianto (STKIP PGRI Trenggalek, 2020)
English used for every reason at university for example English collaborated with business that must be more important in daily uses as the English for specific things or purposes. All we know it as English for Specific Purposes or ESP. Such as in the development of teaching and learning English especially English in university or in ESP we need a media or book in their procedure and its implementation. And for its procedures every materials or book are needs to be appropriates in their materials with the education aspect such as the philosophical aspects on its. On addition philosophical aspect is the main aspect on it that can be a hence to elaborates the material for the student need especially for ESP student. This research objective is to explain the appropriateness of the philosophical aspects by the Hopkin theory in book entitled “Business Basic I” for ESP Student in terms of its contents. The design of this study is descriptive qualitative, and it is taken from documents and material resumed in its book. This research is categorized as qualitative research design because this study is aimed to identify the book toward the criteria of good book and its content. Based on the result and analysis of the research that have been done, the writer can conclude that a book with the title “Business Basic I” was categories in an appropriate and a good book related to the description of the material. And for the interpretation toward the philosophical foundation aspects that consist six aspects such as Clarity, Consistency with the fact, Consistency with Experience, Consistency with other Beliefs, Utility and Simplicity it can be shown that this book run and construct by social reconstruction philosophy and structuralism philosophy. It can be shown from the several philosophical foundation aspects from the data collection result.